2018
DOI: 10.12693/aphyspola.133.1097
|View full text |Cite
|
Sign up to set email alerts
|

ORR Electrocatalysis on Cr3+, Fe2+, Co2+-Doped Manganese(IV) Oxides

Abstract: The ionic dopant additives have different mechanisms of their influence upon MnO2 electrocrystallisation process and depending on dopants added the following polymorphs are stabilised: α-MnO2 (hollandite, I4/m) -NH + 4 ; γ-MnO2 (ramsdellite, P bnm) -Co 2+ , Fe 2+ ; layered polymorph δ-MnO2 (birnessite, C2/m) -Cr 3+ . The defect states of intergrowth method in ramsdellite matrix and twinning, OH groups studied by X-ray diffraction and the Fourier transform infrared mtehod, respectively, indicate their high cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…For this reason, in the last decades, the research attention has been focused on the exploitation of cheaper transition metal oxides as MnO 2 [9,13,14], Co 3 O 4 [15], Fe 3 O 4 [16,17], and so on. Among them, manganese oxides were found to be promising because of the abundance of manganese, low cost, scarce toxicity, relative high activity and presence of several valence states/polymorphic phases [18][19][20]. Moreover, MnO 2 has been extensively studied for supercapacitor applications due to its high specific capacitance [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, in the last decades, the research attention has been focused on the exploitation of cheaper transition metal oxides as MnO 2 [9,13,14], Co 3 O 4 [15], Fe 3 O 4 [16,17], and so on. Among them, manganese oxides were found to be promising because of the abundance of manganese, low cost, scarce toxicity, relative high activity and presence of several valence states/polymorphic phases [18][19][20]. Moreover, MnO 2 has been extensively studied for supercapacitor applications due to its high specific capacitance [18].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the already reported performances of manganese dioxide nano-electrocatalysts rarely achieve the well-performing Pt-or Ru-based materials [21]. Therefore, recent studies were devoted to enhancing its electrochemical features by coupling manganese dioxide with conductive additives like carbon nanotubes [22], polymers [23], graphene [24] and/or by doping with various transition metals (such as Ni [25], V [21], Ce [25], Co [26] and Fe [19]) to improve the electron transport features. For instance, Kim et al [26] reported the 5% Co-doped MnO 2 nanoparticles exhibiting an excellent capacitance retention (of about 97%) after 5000 charge/discharge cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon‐supported composite catalyst of iron phthalocyanine–MnO x was evaluated as a cathode in a MFC, the power density being improved from 66 to 143 mW m −2 after replacing iron phthalocyanine with iron phthalocyanine–MnO x 16 . Birnessite is a crystalline oxide of Mn(IV) and it has been studied extensively over many years, it being synthesized using several methods including chemical methods, 17–22 phase transformation, 23, 24 sol–gel, 25–30 electrochemical oxidation, 31–34 electrodeposition, 35–38 microwave‐assisted methods 39–42 and thermal methods 43–46 . However, for almost 30 years, most birnessite projects were applied for the development of supercapacitors, batteries and sensors, for combustion and for removal of heavy metals, among other applications, whereas birnessite application in MFCs was rarely reported during all this time.…”
Section: Introductionmentioning
confidence: 99%